Asian Pacific Digestive Week (APDW) 2024 - Ali, Md Akmat (The Journal of Ad-din Women's Medical College, 2025)
Abstract not available The Journal of Ad-din Women's Medical College; Vol. 13 (1), Jan 2025; p 39